Connecting School Leaders in an Ethic of Care Community - Thomas, Christy; Martens, Sherry (Journal of Leadership, Accountability and Ethics, 2022)
The role of school administrators continues to expand and intensify leading to decreased dissatisfaction and reported moral distress. There is a need to explore professional learning opportunities for school leaders that allow for trusting, open conversations that build an ‘ethic of care’ (Noddings, 1982). Utilizing narrative inquiry, participant’s stories on their experiences navigating moral distress and the impact of being part of an online ‘ethic of care’ community was analyzed. This study informs those seeking to develop an ‘ethic of care’ community focused on personal leadership development to support school leaders to flourish within a rising context of moral distress.